Academic Self-Efficacy as a Determinant of the Need for Cognition, Parental Involvement, and Extraversion among Secondary School Students in Oyo State, Nigeria - Ajadi, Titilayo Adeoye (Papers in Education and Development, 2023)
This study investigated the need for cognition, parental involvement, and extraversion as factors determining academic self-efficacy among secondary school students in Oyo State, Nigeria. It adopted a correlational type of the descriptive research design. The study used a total sample of 300 secondary school students who were chosen based on a multistage sampling technique. Data were collected by means of a questionnaire focusing on the following variables (Need for Cognition r=0.84; Parental Involvement r=0.83; Extraversion r=0.86; and Self-Efficacy r=0.87). Data were analysed using Pearson Product Moment Correlation Coefficient and Multiple Regression. The results revealed that the need for cognition (r=.804), and parental involvement (r=.788) had a strong positive correlation with academic self-efficacy while extraversion had a weak correlation with academic self-efficacy (r=-.203). Parental involvement was the most potent out of the predictor variables (Î²=.478), followed by the need for cognition (Î²=.365). Extraversion made a negative contribution to the predictor of academic self-efficacy (Î²=-.245). Regression analysis revealed that the three independent variables (need for cognition, parental involvement, and extraversion) jointly accounted for 55.2% (Adjusted R2=.552) variation in the prediction of self-efficacy. The study recommends that school counsellors should counsel students on the need to develop higher academic self-efficacy in order to bring about excellent results in their academics. Keywords: need for cognition, parental involvement, extraversion, academic self-efficacy